In search of value for their money: Banking preferences and service quality perceptions of local and expatriate retail bank customers - Mehtap-Smadi, Salime (My University, 2010)
This study investigates bank selection factors and service quality perceptions of 191 local and expatriate retail bank customers in North Cyprus. The banking industry in this politically non- recognized small island is composed of local banks and branch banks from mainland Turkey. The SERVPERF instrument used in this study proved to be of a five-dimensional nature. Local bank customers indicated that adequate number of tellers, high interest rates on savings and speed and quality of service were the most important bank selection factors, whereas expatriate bank customers indicated that speed and quality of service, low service charges and recommendations of friends were more important. There was a significant difference between local and expatriate bank customers in terms of their service quality perceptions and in particular with regards to the tangibles, assurance and empathy dimensions of the SERVPERF scale. The study provides suggestions for banks to redefine their corporate image to one that is customer-focused and driven by service quality. © International Economic Society.
Keywords: Bank selection factors; Cyprus; Expatriates; Retail banking; SERVPERF